The influence of situational variables on ball possession in the South African Premier Soccer League - Kubayi, A.; Toriola, A. (Journal of Human Kinetics, 2019)
Although the influence of ball possession in soccer has been well studied in other leagues, such information is sparse concerning the South African Premier Soccer League (PSL). The purpose of this study was to assess the impact of situational variables on ball possession in the PSL. Thirty-two matches played during the 2016-2017 PSL season were analysed using a multiple-camera match analysis system (InStat®). Three situational variables (match outcome, match location, and quality of opposition) and team performance variables (percentage of ball possession, ball possession <5 s, ball possession 5-15 s, ball possession 15-45 s, and ball possession >45 s) were examined. The results showed that losing teams had the highest ball possession (52.35 ± 5.90%) compared to winning (47.65 ± 5.90%) and drawing (50.00 ± 9.98%) teams. Playing away significantly (p < 0.05) decreased ball possession by 5.21% compared to playing at home. Playing against weak opposition was associated with increased ball possession by 4.09%. Conclusively, soccer coaches should be aware of the potential role of situational variables in determining successful team performance in a league season.